Negotiators' cognition: An experimental study on bilateral, integrative negotiation - Livia Reina (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
Many negotiations offer a potential for integrative agreements in which the parties can maximize joint gains (through logrolling) without competing for resources as in a 0-sum game; nevertheless negotiators often fail to exploit this potential and settle for suboptimal, distributive agreements. In this study a situation of two-issues bilateral negotiation has been considered. Our aim is to get some insight on the causes that prevent negotiators from reaching integrative, Pareto-optimal agreements. We ran two experiments (one with policy makers and one with students) in which we tested the "fixed pie bias" of negotiators, and we introduced a new explanation for suboptimality, based on the hypothesis of a satisficing (not optimizing) behavior of negotiators, which leads them to a "zone of agreement bias"(ZAB).
Keywords: C91; 330; integrative negotiation; logrolling; cognitive bias; satisficing; Verhandlungstheorie; Beschränkte Rationalität; Test; Theorie; Kognition; Stimmentausch